Diagnostic Impact of Transesophageal Echocardiography in Patients with Acute Cerebral Ischemia. Issue 4 (April 2016) - Pallesen, Lars‐Peder; Ragaller, Margaretha; Kepplinger, Jessica; Barlinn, Kristian; Zerna, Charlotte; Siepmann, Timo; Wiedemann, Baerbel; Braun, Silke; Weise, Matthias; Bodechtel, Ulf; Puetz, Volker
Abstract : Objectives: Transesophageal echocardiography (TEE) is the diagnostic gold standard for the detection of structural heart diseases as potential sources of cardiac emboli in patients with acute cerebral ischemia. We sought to determine the diagnostic yield of TEE in patients with acute ischemic stroke or transient ischemic attack (TIA). Methods: We retrospectively analyzed consecutive patients with acute cerebral ischemia who were admitted to our hospital between October 2008 and December 2011. TEE reports were screened for detection of cardiac source of embolism judged by the recommendation to change medical management. We performed univariate and multivariate analyses to identify predictors of clinically relevant TEE findings among baseline characteristics. Results: Of 3314 patients with ischemic stroke or TIA, TEE was performed in 791 (24%) patients (mean age 64 ± 13 years, 589 [74%] ischemic stroke, 202 [26%] TIA). A potential cardioembolic source was found in 71 (9%) patients with patent foramen ovale with atrial septal aneurysm being the most common finding (24/71 patients, 34%). In multivariate analysis, peripheral vascular disease (OR 2.57; 95%CI 1.00–6.61), imaging evidence of infarction in multiple locations (OR 4.13; 95%CI 1.36–12.58), and infarction in the posterior circulation (OR 2.11; 95%CI 1.01–4.42) were associated with the identification of a potential cardioembolic source with TEE. Conclusion: TEE identified a potential structural cardioembolic source in nearly 10% of our selected patient population with acute ischemic stroke or TIA, thus underlining its diagnostic value. Our data suggest that patients with hitherto unknown stroke etiology should be considered for additional TEE.